'Educity imaginaries'? Escaping mobile policy imaginaries to reimagine educational futures in Auckland. (August 2014) - Lewis, Nick; Kearns, Liam
Abstract Over the last decade, international education initiatives and higher education restructuring in various parts of the world have been increasingly entangled with national knowledge economy policy and urban growth projects. The ensuing entanglements have been more or less 'policied' by what might be termed 'educity imaginaries', which have taken spectacular material form in some global cities. In this paper, we explore the working out of educity imaginaries in Auckland against the backdrop of shifting investment trajectories and the global mobility of educity policy. We argue that globalising imaginaries have intersected with local policy legacies and political economy to produce a mix of mundane and promissory imaginaries. We examine the frictions generated in these encounters and the ways in which they are reworked as resources in local city‐making. Working from a commitment to enactive research, we argue that Auckland City might make much more of the possibilities opened up by 'educity imaginaries'.